2020
DOI: 10.1111/1365-2745.13464
|View full text |Cite
|
Sign up to set email alerts
|

Good things take time—Diversity effects on tree growth shift from negative to positive during stand development in boreal forests

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…This reduces competition for light and allows these communities to grow faster overall, compared to their respective monocultures (Jucker et al, 2015; Sapijanskas et al, 2014). Therefore, the increase in competition associated with the canopy closure and stem exclusion phases seems to be a key factor in allowing conditions for mixtures to overyield through niche partitioning or facilitation (Jucker et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This reduces competition for light and allows these communities to grow faster overall, compared to their respective monocultures (Jucker et al, 2015; Sapijanskas et al, 2014). Therefore, the increase in competition associated with the canopy closure and stem exclusion phases seems to be a key factor in allowing conditions for mixtures to overyield through niche partitioning or facilitation (Jucker et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have analysed the temporal dynamics of diversity effects on productivity during stand development (e.g. Huang et al, 2018; Jucker et al, 2020; Taylor et al, 2020). Furthermore, much less is known about how underlying mechanisms (Complementarity and Selection) drive this relationship through succession (Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the effects of species diversity on tree growth vary during forest succession (Taylor et al., 2020) with biodiversity effects on productivity strengthening from young to middle‐aged forests (Huang et al., 2018; Jucker et al., 2020; Zhang et al., 2012). Time is needed for plant species assemblages in diverse communities to realize the potential niche differentiation in order to optimize the use of limiting resources (Reich et al., 2012; Zuppinger‐Dingley et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our expectation that the diverse native communities should be more resistant against invaders was based on the idea that due to niche complementarity diverse communities should better fill in the available niche space, and thus use more of the available resources (Loreau & Hector, 2001). Possibly, as niche complementarity has been reported to increase over time (Fargione et al, 2007;Jucker et al, 2020), resistance of the native communities against the alien invaders might have increased with diversity if our experiment would have lasted longer.…”
Section: Competition Per Se Rather Than Diversity Plays a More Import...mentioning
confidence: 99%